RESOURCE POTENTIAL OF AGRICULTURAL ENTERPRISES IN THE CONTEXT OF EXTERNAL ENVIRONMENT DIAGNOSIS AND THEIR FUNCTIONING - Sas , L.S.; Kalitsun , Yu.E. (The actual problems of regional economy development, 2023)
The article is devoted to highlight the influence of external environmental factors on the formation of resource potential (human, land, financial, informational, material, technical and technological resources) of an agricultural enterprise. The purpose of the article is to reveal the essence and meaning of the resource potential to ensure the effective functioning of the agricultural enterprise as an open socio-economic system, as well as to determine the influence of environmental factors on the formation of the resource potential using the methodological toolkit of economic diagnostics. The article focuses on the need to diagnosing the external environment of the functioning of agricultural enterprises as an important and necessary prerequisite for the formation of their resource potential. The theoretical influence of external environmental factors on the formation of resource potential of agricultural enterprises is substantiated. Taking into account the sectoral specificity of activity - seasonality of production, dependence on natural and climatic conditions, etc., the main factors of the external environment that influence the formation of the resource potential of agricultural enterprises are defined as: demographic, educational, globalization, informational, institutional, social and cultural, the level of scientific and technical progress, level of economic development. The role of economic diagnostics in studying the external factors affecting the activities of agricultural enterprises is revealed. The methodical toolkit of economic diagnostics is considered and the expediency of using SWOT analysis is substantiated in order to find out the influence of environmental factors on the resource provision of agricultural enterprises. It has been proven that the formation of resource potential in agricultural enterprises, in accordance with modern market requirements, requires taking into account the impact of a range of external factors on the internal environment of the enterprise. The information obtained through diagnostic research enables the economically viable and justified formation of resources that create real and potential opportunities for the functioning, growth and development of agricultural enterprises, ensuring competitive advantages in the market.